POLYCYCLIC AROMATIC HYDROCARBONS (PAHs) IN INDRAMAYU COASTAL, WEST JAVA: DISTRIBUTION, SOURCE, AND ECOLOGICAL RISK ASSESSMENT - Yogaswara, Deny; Falahudin, Dede; Wulandari, Ita; Edward, Edward; Rositasari, Ricky; Shofarudin, Ukis (Marine Geological Institute of Indonesia, 2024)
PAH pollutants from anthropogenic activities were released into Indramayu Coast and could potentially have negative effects on the environment. This study aimed to determine the distribution, source, and ecological risks of PAHs in the area. Seawater and sediment samples were collected and stored in glass bottles at 4 °C and then further processed in the laboratory. The samples were extracted with dichloromethane and n-hexane and then fractionated using a silica gel column, and finally injected into a Gas Chromatography-Mass Spectrometer (GCMS). The distribution of PAH compounds was detected in all sampling stations in varying amounts. PAH with low molecular weight (two to three rings) was predominant in seawater samples, while high molecular weight (four rings) was predominant in sediments. In addition, by using the molecular diagnostic ratio, the PAH source in Indramayu Coast was detected to be pyrogenic and petrogenic processes that come from anthropogenic activities. Exposure to PAH concentrations in this study posed a lower risk to sediment-dwelling organisms. However, further awareness and periodic monitoring are required to detect carcinogenic PAHs.